Synthesis and application of diazenyl sulfonamide-based schiff bases as potential BRCA2 active inhibitors against MCF-7 breast cancer cell line - Olia Rezaeianzadeh; Sakineh Asghari; Mahmood Tajbakhsh; Asieh Khalilpour; Sergey Shityakov (Scientific Reports)
Abstract In this study, a library of novel sulfonamide-based Schiff bases 3a-j was synthesized in high yield (75 to 89%). The FTIR, 1H NMR, and 13C NMR spectroscopic techniques and mass analysis were used to characterize the synthesized compounds. Their anticancer activity was assessed in vitro on the breast cancer (MCF-7) and healthy human breast epithelial (MCF-10 A) cell lines over 48 and 72 h using the MTT assay. Most of the synthesized compounds demonstrated promising activity, with compound 3i showing particularly high efficacy at 48 and 72 h (IC50 = 4.85 ± 0.006 and 4.25 ± 0.009 µM) against the MCF-7 breast cancer cell line. Furthermore, molecular docking studies were performed for compounds 3a-j with the PDB: (3UV7) protein of the breast cancer susceptibility gene 2 (BRCA2). The obtained results revealed that compound 3i has the strongest binding affinity energy (-7.99 kcal/mol), consistent with the obtained experimental data. Additionally, molecular dynamics (MD) simulation assays confirm the formation of a stable 3i-BRCA2 complex with strong binding affinity through the formation of hydrogen bonds. Antioxidant activities were determined by in vitro assay DPPH cation radical activity method. Interestingly, the compound 3j (IC50 = 12.36 ± 0.55 µM) had comparable activity with ascorbic acid (IC50 = 13.58 ± 0.38 µM) in the antioxidant assay. The results of this research could potentially contribute to the development of new therapeutic agents useful in fighting caused by breast cancer.